A Constrained South African Electricity Supply Chain - What Next? - Mathu, Kenneth (European Journal of Applied Sciences, 2023)
Background: The South Africa’s reliance on fossil-fuels for electricity generation for nearly a century, has transformed the nation into a carbon economy, with a heavy carbon footprint, as over 80% of electricity generation and 40% of fossil-fuel production are from coal. The under-serviced aged coal-fired stations, hitherto fail to meet the generation capacity that has contributed power cuts for over a decade. This study explored the constraints of electricity supply chain that culminated into power outages since 2008 covering the aged coal-fired power stations and independent power producers (IPPs) that produces renewable sources of energy. Method: Qualitative research methodology and constructivism research paradigm were pursued, and theories of competitive advantage and sustainable development underpinned the study. The non-probability sampling process was used and interviews were recorded and transcribed. The emanating data was interpreted, coded and analysed via content analysis. Results: The results indicated urgent need for hiring maintenance expertise for the aged coal-fired power stations to minimise loadshedding, while also expediting renewable sources of energy development for the sustainability of electricity supply chain. Conclusion: The outcome of the study would align with the country’s chosen path of “Just Energy Transition” strategy, which embraces clean energy development from renewable sources.